An In-depth Analysis of Online Marketing Strategies for Uplifting Sales at UMKM - Syamsul Arifin; Widya Nurjannah; Zulviar Anas (CV Pena Jaya Pers, 2024)
This study aims to determine the online marketing strategy implemented by MSME Elvin Snack Banana Chips to increase sales. Collect data through observation, interview, document techniques. Data analysis is done by identifying problems, categorizing data, presenting data and drawing conclusions. The results of this study indicate that the marketing strategy to increase sales at MSME Elvin Snack Lamongan Banana Chips in addition to cooperating with stores and agents as well as implementing online marketing strategies, namely product marketing through social networks like Whatsapp and Instagram.